Severe Pediatric TBI Management in a Middle-Income Country and a High-Income Country: A Comparative Assessment of Two Centers - Arango, Jorge I.; George, Laeth; Griswold, Dylan P.; Johnson, Erica D.; Suarez, Maria N.; Caquimbo, Laura D.; Molano, Milton; Echeverri, Raul A.; Rubiano, Andres M.; Adelson, P. David (Frontiers in Surgery, 2021)
Background: TBI is a global public health issue with over 10 million deaths or hospitalizations each year. However, access to specialized care is dependent on institutional resources and public health policy. Phoenix Children’s Hospital USA and the Neiva University Hospital Colombia compared the management and outcomes of pediatric patients with severe TBI over five years to establish differences between outcomes of patients managed in countries of varying resource availability. Methods: We conducted a retrospective review of individuals 0 to 17 years of age, with a diagnosis of severe TBI and admitted to PCH and NUH between 2010 and 2015. Data collected included Glasgow Coma Scores, intensive care unit monitoring, and Glasgow Outcome Scores. Pearson Chi-square, Fisher exact, T-test or Wilcoxon-rank sum test were used to compare outcomes. Results: 101 subjects met inclusion criteria. NUH employed intracranial pressure monitoring less frequently than PCH (p=0.000), but surgical decompression and subdural evacuation were higher at PCH (p=0.031 and p=0.003). Mortality rates were similar between institutions (15 % PCH, 17% NUH) as were functional outcomes (52% PCH, 54% NUH). Conclusions: Differences between centers included time to specialized care and utilization of monitoring. No significant differences were evidenced in survival and overall functional outcomes.